Worked Example-Based Instruction to Reduce Cognitive Load and Academic Boredom in Mathematics Learning - Syahrina Anisa Pulungan; Ainul Marhamah Hasibuan; Nurdalilah Nurdalilah (Journal of Mathematics Instruction, Social Research and Opinion, 2026)
This study investigates how cognitive load influences learning outcomes by considering the role of academic boredom, while also examining the effectiveness of worked example-based instruction in reducing both cognitive load and academic boredom in mathematics learning. The research employed a quasi-experimental design involving experimental and control groups with a total of 120 participants (n = 120). Data were collected using questionnaires measuring cognitive load and academic boredom, along with tests assessing learning outcomes. The relationships among variables, both direct and indirect, were examined using Partial Least Squares Structural Equation Modelling (PLS-SEM). The results show that an increase in cognitive load tends to be associated with higher levels of academic boredom and a decline in learning outcomes. Academic boredom negatively predicts learning outcomes and acts as a mediating variable between cognitive load and achievement. Worked example-based instruction demonstrates a stronger ability to regulate cognitive and emotional processes compared with traditional instructional approaches. These results underscore the need to maintain an appropriate balance between cognitive demands and students’ emotional engagement in mathematics learning. The study offers a contribution by combining cognitive and affective aspects within a unified analytical perspective and presents practical recommendations for developing instructional strategies that foster cognitive-emotional balance.